Decision-Making for an Incapacitated Pregnant Patient - Mabel, Hilary (The Hastings Center report, 2017)
Decisions about continuing or terminating a pregnancy touch on profound, individualized questions about bodily integrity, reproductive autonomy, deeply held values regarding one's capacity for parenthood, and, in the case of a high-risk pregnancy, the risks one is willing to take to have a baby. So far as possible, reproductive decisions are made between a patient, in some cases her partner, and her medical provider. However, this standard framework cannot be applied if the patient lacks decision-making capacity. In this essay, we discuss one such case that came before our clinical ethics team. We describe the challenges of respecting a patient's reproductive preferences when the patient cannot share what those preferences are, and we argue that decisions regarding reproductive health care should not be treated with exceptionalism. Rather, they should proceed under the normal processes of surrogate decision-making, including the application of substituted judgment. This approach enables us to take the patient's values into account when considering the questions implicated in reproductive health care, just as we do for other kinds of health care decisions in which a patient's deeply held values are salient.